Characteristics of Physical Fitness and Cardiometabolic Risk in Chinese University Students with Normal-Weight Obesity: A Cross-Sectional Study - Tian Q (Dove Medical Press, 2020)
Qianqian Tian,1 Hui Wang,2 Keneilwe Kenny Kaudimba,1 Shanshan Guo,1 Haixin Zhang,1 Song Gao,1 Ruwen Wang,1 Xin Luan,1 Jason Kai Wei Lee,3– 5 Peijie Chen,1 Tiemin Liu,2 Ru Wang1 1School of Kinesiology, Shanghai University of Sport, Shanghai, People’s Republic of China; 2State Key Laboratory of Genetic Engineering, Department of Endocrinology and Metabolism, Institute of Metabolism and Integrative Biology, Human Phenome Institute, School of Life Sciences, Zhongshan Hospital, Fudan University, Shanghai, People’s Republic of China; 3Department of Physiology, Yong Loo Lin School of Medicine, National University of Singapore, Singapore; 4Global Asia Institute, National University of Singapore, Singapore; 5N.1 Institute for Health, National University of Singapore, SingaporeCorrespondence: Tiemin LiuState Key Laboratory of Genetic Engineering, Department of Endocrinology and Metabolism, Institute of Metabolism and Integrative Biology, Human Phenome Institute, School of Life Sciences, Zhongshan Hospital, Fudan University, Shanghai, People’s Republic of ChinaTel/Fax +86-21- 31246765Email tiemin_liu@fudan.edu.cnRu WangSchool of Kinesiology, Shanghai University of Sport, Shanghai, People’s Republic of ChinaTel/Fax +86-21-65507351Email wangru@sus.edu.cnPurpose: To (i) describe the characteristics of physical fitness and cardiometabolic risk in Chinese university students with normal-weight obesity (NWO); (ii) assess the association between NWO with physical fitness and cardiometabolic risk.Methods: A total of 249 participants from the 2018 Shanghai University of Sport Alumni Health Cohort Study in China formed the study cohort. NWO was defined as normal body mass index (17.9– 23.9 kg/m2 for males; 17.2– 23.9 kg/m2 for females) but with excess body-fat percentage (≥ 20% for males; ≥ 30% for females). Body composition was assessed by dual-energy X-ray absorptiometry. Physical-fitness scores were calculated from a battery of sex-specific tests. Cardiometabolic risk was calculated using a continuous clustered risk (MetS) score.Results: We found that 16.7% of male and 45.3% of female university students were classified as having NWO. Participants with NWO showed worse cardiorespiratory fitness than those with normal weight (NW) (male NWO (37± 8) vs male NW (41± 6) mL/kg/min, p< 0.01; female NWO (31± 4) vs female NW (33± 6) mL/kg/min, p< 0.01). NWO was associated negatively with the fitness score (OR = 0.853; 95% CI = 0.793– 0.917) and was associated positively with the MetS score (1.280; 1.162– 1.410).Conclusion: University students with NWO were characterized by higher cardiometabolic risk and lower levels of physical fitness. Our findings implied that university students with NWO should be mindful of the potential hidden health risks of excess body fat and participate in exercise to enhance physical fitness.Keywords: body composition, body mass index, body fat distribution, skeletal muscle, public health